Letter from the Democratic Task Force National Women's Political Caucus - Mildred Jeffrey::::::; Koryne Horbal::::::; Patt Derian:::::: (1976)
This June 1976 letter from the Democratic Task Force and Democratic Women's Caucus provides delegates and alternates with a pre-convention update and invites them to participate in Women's Caucus activities. It announces a reception honoring women delegates, caucus meetings at the Statler Hilton, and the establishment of a Women's Political News Service to highlight women delegates' contributions. The letter reports that most goals of the Democratic Women's Agenda were incorporated into the party platform, including opposition to a constitutional amendment banning abortion. However, a proposed rule requiring equal division of male and female delegates at future conventions was defeated and replaced by a weaker resolution, prompting the filing of a minority report seeking delegate support. The letter also notes passage of a Charter amendment strengthening affirmative action and urges women delegates to submit biographies and photographs to assist press outreach.